2010
DOI: 10.3899/jrheum.090681
|View full text |Cite
|
Sign up to set email alerts
|

Association of theMCP-1−2518 A/G Polymorphism and No Association of Its ReceptorCCR2−64 V/I Polymorphism with Lupus Nephritis

Abstract: These findings support that MCP-1 -2518 G/G is associated with LN but there was no association of this genotype with renal function or renal survival. When studying CCR2 -64 V/I polymorphism we showed a positive association of the V allele with healthy controls but no association of the genotype with LN patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…This mutation has not been studied extensively in inflammatory disease, but a few publications have assessed the association of this SNP with pathology. No association was found with the incidence or severity of RA (Bayley et al, 2003) or with systemic lupus erythematosus [SLE (Aguilar et al, 2003)], and similarly the mutation did not correlate with the incidence of lupus nephritis, although the V allele was associated with 56 a less severe disease phenotype as measured by the SLEDAI (SLE disease activity) index (Malafronte et al, 2010). Interestingly, carriers of the I allele with psoriasis were found to be more likely to progress to psoriatic arthritis once the disease was established, but CCR2 genotype did not correlate with the incidence of psoriasis per se (Soto-Sanchez et al, 2010).…”
Section: B Ccr2mentioning
confidence: 99%
“…This mutation has not been studied extensively in inflammatory disease, but a few publications have assessed the association of this SNP with pathology. No association was found with the incidence or severity of RA (Bayley et al, 2003) or with systemic lupus erythematosus [SLE (Aguilar et al, 2003)], and similarly the mutation did not correlate with the incidence of lupus nephritis, although the V allele was associated with 56 a less severe disease phenotype as measured by the SLEDAI (SLE disease activity) index (Malafronte et al, 2010). Interestingly, carriers of the I allele with psoriasis were found to be more likely to progress to psoriatic arthritis once the disease was established, but CCR2 genotype did not correlate with the incidence of psoriasis per se (Soto-Sanchez et al, 2010).…”
Section: B Ccr2mentioning
confidence: 99%
“…9 Urinary MCP-1 levels have been shown to be positively correlated with the degree of proteinuria in children with FSGS and IgA nephropathy. 10 There are several studies reporting the relationship between MCP1 2518 A/G polymorphism and prognosis of various renal diseases such as IgA nephropathy, 11,12 diabetic nephropathy 13 and lupus nephritis, 14 however the association of this polymorphism with the clinical outcome in primary FSGS has not been determined yet. The aim of this study was to investigate the relationship between MCP1 2518 A/G polymorphism and urinary-serum MCP-1 levels with the incidence and clinical course of children with primary FSGS.…”
Section: Introductionmentioning
confidence: 99%
“…Malafronte et al also had reported that GG genotype were associated with LN among Brazilian SLE patients [35]. Difference in the reports showing distribution and effect of G allele on the disease is attributed to the demographic diversification of populations.…”
Section: Discussionmentioning
confidence: 94%